2015
DOI: 10.1016/j.gep.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Changes in microRNA expression during differentiation of embryonic and induced pluripotent stem cells to definitive endoderm

Abstract: Pluripotent stem cells, including embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs), have the potential to treat type 1 diabetes through cell replacement therapy. However, the protocols used to generate insulin-expressing cells in vitro frequently result in cells which have an immature phenotype and are functionally restricted. MicroRNAs (miRNAs) are now known to be important in cell fate specification, and a unique miRNA signature characterises pancreatic development at the definitive end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
(267 reference statements)
0
2
0
Order By: Relevance
“…These studies revealed that two of the most highly expressed miRNAs in adult liver and pancreas, namely miR-122 and miR-375, are also amongst the most highly induced miRNAs during the differentiation of ESCs into definitive endoderm (Tzur et al, 2008; Hinton et al, 2010; Kim et al, 2011; Francis et al, 2015). MiR-30d and miR-200a are also induced during the differentiation of hESC into definitive endoderm whereas miR-151a-5p and miR-151-a-3p were up-regulated in differentiated hESCs (Migliorini et al, 2014; Francis et al, 2015). Chen et al group have shown that miR-186, -199a, and -339 are found at higher levels in islet-like insulin-positive cell clusters derived from the differentiation of hESC (Joglekar et al, 2009b).…”
Section: Perspectives For Future Studymentioning
confidence: 99%
“…These studies revealed that two of the most highly expressed miRNAs in adult liver and pancreas, namely miR-122 and miR-375, are also amongst the most highly induced miRNAs during the differentiation of ESCs into definitive endoderm (Tzur et al, 2008; Hinton et al, 2010; Kim et al, 2011; Francis et al, 2015). MiR-30d and miR-200a are also induced during the differentiation of hESC into definitive endoderm whereas miR-151a-5p and miR-151-a-3p were up-regulated in differentiated hESCs (Migliorini et al, 2014; Francis et al, 2015). Chen et al group have shown that miR-186, -199a, and -339 are found at higher levels in islet-like insulin-positive cell clusters derived from the differentiation of hESC (Joglekar et al, 2009b).…”
Section: Perspectives For Future Studymentioning
confidence: 99%
“…Micro ribonucleic acids (microRNAs, miRs) are endogenous short non-coding RNAs. They have important regulatory functions in a wide range of biological processes, including regulating cell proliferation, apoptosis, and aging [ 5 ]. In addition, they are also involved in the development of the heart and the regeneration of the myocardium [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…miR-27b, a highly conserved miRNA across vertebrates, has been shown to regulate various target genes involved in signaling pathways 14,15 . In previous studies, miR-27b expression has been upregulated through differentiation from definitive endoderm to hepatocytes 8,16,17 and the miR-23b cluster, which encodes miR-23b~27b~24, regulates hepatic differentiation by targeting SMAD3/4/5, the downstream molecules of the TGF-β superfamiliy 14 . In mouse oocyte, expression level of miR-27b was decreased after fertilization and remained low during subsequent cell proliferations 10 , suggesting that downregulation of miR-27b expression is a critical step to drive embryonic development.…”
mentioning
confidence: 96%